University of Maryland launches new Do Good Initiative. Issue 326 (November 2016) - Unknown
Abstract : The University of Maryland has launched a new initiative aimed at creating a permanent and visible entity on campus that will become a hub of activity for philanthropy, nonprofit management, public policy, social change and leadership. Central to the Do Good Initiative will be the Do Good Institute, a center of research and thought leadership in philanthropy and social change. From orientation to graduation, the Do Good Institute will engage the entire student body in initiatives aimed at ensuring every student will be informed and motivated to "do good" in their communities, both local and worldwide, the university said.